ANALISA SISTEM RESERVASI TIKET PADA PT XYZ - G. Gani, Alcianno (Universitas Dirgantara Marsekal Suryadarma, 2019)
The use of the computer and its systems has become a major necessity to improve the the company performance. Each of the company's manual processes can be subtituted by computers because of the provision of more sophisticated information and to support the decision making process undertaken by management. PT XYZ is engaged in serving the Tourism Services Business travel and requested by one airline of Saudi Arabia, AIR NAS (National Air Service) to become a GSA (Ground Service Agent) official in Indonesia on 19 November 2012. As Ground Service Agent (GSA), PT XYZÂ serves Umrah flight ticket sales. In the system analysis conducted by the author is found a problems in the system include: the lack of a computerized and automation systems that can make the work more efficient , the reservation process is still done manually so that the customer must come to the office , the process of checking and inputting the data of available seat still done manually cause inefficient of time, the manual reporting process by collecting data from payment and ticket printing so spend much time , the ticket printing process is inefficient because after payingÂ the consumer must return again to the reservation. In order to minimize the existing problems, it is needed to develop information systems and computerized ticket reservation web-based in PT XYZ Keywords: Information System, Analyse, Reservations, Tickets